UN Security Council decision-making: testing the bribery hypothesis - EUGENIO PACELLI LAZZAROTTI DINIZ COSTA (Revista Brasileira de Política Internacional, 2014)
Liberal-Institutionalism and Structural Realism expectations about international organizations are confronted by looking at if and how US-controlled international aid is granted, and particularly if it is related or not to political affinity and to United Nations Security Council (UNSC) non-permanent membership. A preliminary assessment suggests that these relations only hold for the period of the Cold War, and, even then, only when UNSC non-permanent membership is in years in which the Security Council was deemed very important.